Advanced LSI-based amperometric sensor array with light-shielding structure for effective removal of photocurrent and mode selectable function for individual operation of 400 electrodes. Issue 3 (8th December 2014) - Inoue, Kumi Y.; Matsudaira, Masahki; Nakano, Masanori; Ino, Kosuke; Sakamoto, Chika; Kanno, Yusuke; Kubo, Reyushi; Kunikata, Ryota; Kira, Atsushi; Suda, Atsushi; Tsurumi, Ryota; Shioya, Toshihito; et al.
Abstract : We report an advanced type of LSI-based amperometric sensor array with an effective light shield. Abstract : We have developed a large-scale integrated (LSI) complementary metal-oxide semiconductor (CMOS)-based amperometric sensor array system called "Bio-LSI" as a platform for electrochemical bio-imaging and multi-point biosensing with 400 measurement points. In this study, we newly developed a Bio-LSI chip with a light-shield structure and a mode-selectable function with the aim of extending the application range of Bio-LSI. The light shield created by the top metal layer of the LSI chip significantly reduces the noise generated by the photocurrent, whose value is less than 1% of the previous Bio-LSI without the light shield. The mode-selectable function enables the individual operation of 400 electrodes in off, electrometer, V1, and V2 mode. The off-mode cuts the electrode from the electric circuit. The electrometer-mode reads out the electrode potential. The V1-mode and the V2-mode set the selected sensor electrode at two different independent voltages and read out the current. We demonstrated the usefulness of the mode-selectable function. First, we displayed a dot picture based on the redox reactions of 2.0 mM ferrocenemethanol at 400 electrodes by applying two different independent voltages using the V1 and V2 modes. Second, we carried out a simultaneous detection of O2 and H2 O2 using the V1 and V2 modes. Third, we used the off and V1 modes for the modification of the osmium-polyvinylpyridine gel polymer containing horseradish peroxidase (Os-HRP) at the selected electrodes, which act as sensors for H2 O2 . These results confirm that the advanced version of Bio-LSI is a promising tool that can be applied to a wide range of analytical fields.